Effect of Neo-Boost Pesticide on Mortality and Development of Different Life Stages of Two-Spotted Spider Mite, Tetranychus urticae - Bruinsma, Kristie; Salehipourshirazi, Golnaz; Zhurov, Vladimir; Dagher, Fadi; Grbic, Miodrag; Grbic, Vojislava (Frontiers in Agronomy, 2021)
The two-spotted spider mite, Tetranychus urticae, is a polyphagous agricultural pest that feeds on over a thousand plant species and more than 150 crops. Its status as an agricultural pest is exacerbated by its outstanding potential to evolve resistance to pesticides. The existence of multiresistant mite populations challenges mite management and creates a need for the development of pesticides with novel modes of action. In this study, we evaluated the acaricidal activity of Neo-Boost, a biopesticide registered as a bactericide/fungicide/insecticide/miticide. Peroxyacetic acid and potassium silicate are listed as active ingredients in the Neo-Boost formulation. Using the recommended field dose, we tested contact and residual effects of Neo-Boost on T. urticae egg, larval, and adult life stages. We found that Neo-Boost had no ovicidal effect but was effective against larvae (mortality of 87% over 48 hours post-treatment) and larval developmental progression. On the adult mites, Neo-Boost acted as a deterrent and caused moderate mortality of 35%. Neo-Boost showed efficacy similar to the positive control AGRI-mek SC (ative ingredient abamectin) on larval mortality whereas Neo-Boost had an intermediate effect on adults compared to AGRI-mek SC. We also tested the proposed ability of Neo-Boost to induce a systemic response, however, it had no priming effect on treated tomato plants against mites. Of the individual Neo-Boost components tested, the active compounds peracetic acid and silica were not effective in any assay. However, sodium percarbonate, surfactant, and other components were sufficient for the full effectiveness of Neo-Boost formulations. Additionally, phytotoxicity was rare and minor when it occurred. Overall, despite the inefficiency of active compounds, the Neo-Boost formulation, either in its original or simplified formulation, may be useful for mite control on crops that are destined for fresh human consumption or medicinal use.